Montevideo - Diagonale. (Antwerpen : Montevideo, 1983)
Blacker, Kate ; Walter Daems ; DE Jong, Rob ; Van Evelo, Udo G. ; Di Rosa, Richard ; Dornseif, Frank ; Gentils, Frans ; De Coninck, Frankie ; Gentils, Paul ; Gentils, Vic ; Gherban, Alexandre ; Glasker, Horst ; Grossen, Luc ; Hien, Albert ; Julius ; Kemps, Niek ; Kramer, Michael ; Kummer, Raimund ; Pitz, Hermann ; Lohaus, Bernd ; Luy, Wolfgang ; Mach, David ; Maes, Herman ; Mang, Rainer ; Metzel, Olaf ; Mosta Heirt, Come ; Pacquee, Ria ; Rohling, Gerd ; Rombouts, Guy ; Saytour, Patrick ; Shirakawa ; Uematsu, Keiji ; Van de Velde, Ludwig Van Snick, Philippe ; Vercammen, Wout ; Visch, Henk ; Voordeckers, Jurgen ; Wolff, Carl Emanuel ; Wurm, Erwin ; Zempel, Jerilea
Montevideo - Diagonale, Montevideo, Kattendijkdok - Westkaai, Antwerpen, 11 juni - 25 september 1983
boek